The COVID-19 cannabis health study: Results from an epidemiologic assessment of adults who use cannabis for medicinal reasons in the United States. Issue 1 (1st December 2020) - Vidot, Denise C.; Islam, Jessica Y.; , Marlene Camacho-Rivera; Harrell, Melissa B.; Rao, Devika R.; Chavez, Jennifer V.; , Lucas G. Ochoa; Hlaing, WayWay M.; Weiner, Michelle; Messiah, Sarah E.
Abstract: Background : Clinical indications for medicinal cannabis include chronic conditions; thus users (MCUs) are at an increased risk of morbidity and mortality resulting from SARS-CoV-2 infection (COVID-19). The study aimed to provide data on cannabis use and self-reported behavioral changes among MCUs with preexisting chronic conditions in response to the pandemic. Methods: An internet-based questionnaire was administered to adults ≥18 who self-reported medicinal cannabis use within the past year. Data are from respondents between March 21 and April 23, 2020; response rate was 83.3%. Health conditions and cannabis frequency, route, and patterns of use were assessed via the COVID-19 Cannabis Health Questionnaire (Vidot et al. 2020). Results: Participants ( N  = 1202) were predominantly non-Hispanic white (82.5%) and 52.0% male (mean age 47.2 years). Mental health (76.7%), pain (43.7%), cardiometabolic (32.9%), respiratory (16.8%), and autoimmune (12.2%) conditions were most reported. Those with mental health conditions reported increased medicinal cannabis use by 91% since COVID-19 was declared a pandemic compared to those with no mental health conditions (adjusted odds ratio: 1.91, 95% CI: 1.38–2.65). 6.8% reported suspected COVID-19 symptoms. Two percent (2.1%) have been tested for COVID-19 with only 1 positive test result. Some MCUs (16%) changed their route of cannabis administration, switching to nonsmoking forms. Conclusions: The majority of MCUs reported at least one preexisting chronic health condition. Over half report fear of COVID-19 diagnosis and giving the virus to someone else; yet only some switched from smoking to nonsmoking forms of cannabis. Clinicians may consider asking about cannabis use among their patients, particularly those with chronic health conditions.